The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s40659-020-00303-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered thalamic neurotransmitters metabolism and functional connectivity during the development of chronic constriction injury induced neuropathic pain

Abstract: Background: To investigate the thalamic neurotransmitters and functional connections in the development of chronic constriction injury (CCI)-induced neuropathic pain. Methods: The paw withdrawal threshold was measured by mechanical stimulation the right hind paw with the von frey hair in the rats of CCI-induced neuropathic pain. The N-acetylaspartate (NAA) and Glutamate (Glu) in thalamus were detected by magnetic resonance spectrum (MRS) process. The thalamic functional connectivity with other brain regions wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…For instance, ALFF was reported to be increased in the post- and precentral gyrus, paracentral lobule, supplementary motor area, and anterior cingulate cortex, and this feature may be associated with the neuropathology of chronic low back pain ( 6 ). ReHo was decreased in the thalamus in neuropathic pain ( 7 ), and ReHo values in abnormal brain regions were associated with pain intensity in postherpetic neuralgia patients ( 8 ). In addition, functional connectivity (FC), which is used to assess brain activity synchronization between any set of brain areas, was reported to be increased in the insular cortex in our previous study on trigeminal neuralgia ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ALFF was reported to be increased in the post- and precentral gyrus, paracentral lobule, supplementary motor area, and anterior cingulate cortex, and this feature may be associated with the neuropathology of chronic low back pain ( 6 ). ReHo was decreased in the thalamus in neuropathic pain ( 7 ), and ReHo values in abnormal brain regions were associated with pain intensity in postherpetic neuralgia patients ( 8 ). In addition, functional connectivity (FC), which is used to assess brain activity synchronization between any set of brain areas, was reported to be increased in the insular cortex in our previous study on trigeminal neuralgia ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Global brain signal regression was not performed because it can cause correlation coefficient redistribution and ambiguous interpretation of negative correlations of FC. (6) To make inter-subject comparisons feasible, individual functional images were warped to standard Montreal Neurological Institute (MNI) space through spatial normalization (7). Detrending was applied to reduce the systematic signal drift with time using a linear model.…”
mentioning
confidence: 99%
“…Alternately, stronger rsFC could reflect cortical disinhibition, a compensatory mechanism to magnify weaker sensory input from a damaged nerve to maintain sensory perception in the hand, 22 as proposed to occur in patients whose median nerves were transected and subsequently repaired. 29 A rodent model of chronic nerve constriction found enhanced thalamic-S1 FC during the development of neuropathic pain, 73 and stronger thalamic-S1 rsFC compared with HCs has been reported in other chronic pain conditions 74–76 including upper extremity neuropathic pain, where stronger thalamic-S1 FC was associated with lower tactile acuity and weaker FC was linked with higher pain scores. 77 Conversely, diabetic-neuropathy patients show reduced thalamic-S1 FC, particularly those with mechanical hyperalgesia.…”
Section: Discussionmentioning
confidence: 94%
“…Research reports have illustrated that metabolic dysregulation performs a central function in NP and that there is cross-talk between metabolic, inflammatory, and immune responses in NP [ 17 ]. Previous studies have shown that NP led to metabolic changes in serum and spinal cord; changes in thalamic neurotransmitter metabolism have also been reported [ 18 ]. Functional enrichment analysis in bioinformatic investigations on NP revealed that the majority of the downmodulated genes are linked to pathways including positive modulation of protein kinase B signaling, phospholipid metabolic activities, and metabolism of xenobiotics by cytochrome P450 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%